Pain Assessment for Adult Patients Admitted to Coronary Care Units in Al - hilla Teaching Hospitals, Babylon – Iraq - Amina Abd Al Hassan Jabur (Journal of Global Pharma Technology, 2018)
Background: Pain considered as a significant problem for critically ill patients, pain assessment is essential toreach optimal level of quality of care. Nurses play a critical role in managing and alleviating acute pain amongcritically ill adult patients. Objectives: To assess the level of pain of critically ill adult patients who wereadmitted to the coronary care units in Al-hilla teaching hospitals. Methodology: A descriptive cross-sectionalstudy design selected to assess pain for critically ill patients who were admitted to coronary care units in Al-hilla teaching hospitals was conducted from October 2016 through August 2017. Non-probability (purposive)sample consisted of 92 patients selected, structured questionnaire which consist five parts were prepared inorder to collect the data. The statistical package version 22 was used to analyze the data. Results: Malepatients were predominated, the majority age group of participants were (41 to 65) years constituted 62%most of them were married with low level of education, regarding smoking habit 52% of them were smokers.High proportion of patients 83.7% had frequent bouts of pain while 35.9% were suffering from persistent pain;the most associated symptom with pain was drowsiness (77.2%). About two third of the participants preferredto use medications to control their pain, according to McGill questionnaire the mean score of pain intensity forthe study sample was severe (2.50). Conclusion: Pain still unresolved problem among adult patients admittedto the coronary care units in Al hilla teaching hospitals who recorded severe pain, which accompanied withassociated symptoms such as drowsiness. Recommendation: There is a need for focused continuouseducation and training program to important the health personnel's practice and knowledge regarding painassessment and management.Keywords: Pain Assessment, Adults Patients, Critical care units, McGill Pain Questionnaire.